The catalytic efficiency of METTL16 affects cellular processes by governing the intracellular S-adenosylmethionine setpoint - Juliana N. Flaherty; Enakshi Sivasudhan; Matthew Tegowski; Zheng Xing; Madeline M. McGinnis; Olga V. Hunter; Kyah M. Featherston; Komal Sethia; Benjamin P. Tu; Kate D. Meyer; Nicholas K. Conrad (Cell Reports)
Summary: The methyl donor S-adenosylmethionine (SAM) regulates many cellular processes. The N6-methyladenosine (m6A) methyltransferase METTL16 regulates the expression of the SAM synthetase MAT2A, but the consequences of this regulation are not well documented. Here, we used a degron and complementation strategy in HCT116 cells to demonstrate that disruption of MAT2A regulation by METTL16 influences SAM-dependent processes including histone methylation, translation, and RNA methylation. We also identify U6 snRNA pseudogenes as METTL16 substrates. Complementation by a catalytically hyperactive METTL16 complements its methyltransferase activities but decreases intracellular SAM concentrations by abrogating MAT2A regulation. Moreover, these cells are hypersensitive to treatment with a MAT2A inhibitor and to deletion of the MTAP gene, which is lost in ∼15% of cancers. These findings support the conclusion that the catalytic efficiency of METTL16 helps establish the SAM setpoint in cells and suggest that this function could be exploited as a treatment for MTAP-deficient cancers.